Investigation of the influence of isovalent impurity of silicon and y-irradiation (⁶⁰Co) on electrophysical parameters of n-Ge <Sb> - Gaidar, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The influence of isovalent impurity of Si on the kinetics of electron processes
in n-Ge <Sb> single crystals has been investigated. It has been shown that in the region of
predominant impurity scattering (at Т = 77.4 K), the presence of isovalent impurity
significantly reduces the mobility of charge carriers and changes the sign of inequality
ne₃₀₀k / ne₇₇.₄k > 1 characteristic of n-Ge <Sb> single crystals to the opposite one. It has
found that in n-Ge <Sb> samples irradiated by y-rays (⁶⁰Co) with the dose 1.23*10⁸ R, the
charge carrier mobility has low radiation stability and decreases with increasing the
magnetic field, while remaining practically unchanged in the region of the intermediate
Н values.